Non-contiguous finished genome sequence and description of Salmonella enterica subsp. houtenae str. RKS3027. Issue 2 (March 2013) - Zhu, Songling; Wang, Hong-Liang; Wang, Chunxiao; Tang, Le; Wang, Xiaoyu; Yu, Kai-Jiang; Liu, Shu-Lin
Abstract Salmonella enterica subsp. houtenae serovar 16:z4, z32:— str. RKS3027 was isolated from a human in Illinois, USA.S. enterica subsp. houtenae is a facultative aerobic rod-shaped Gram-negative bacterium. Here we describe the features of this organism, together with the draft genome sequence and annotation. The 4, 404, 136 bp long genome (97 contigs) contains 4, 335 protein-coding gene and 28 RNA genes.